2022
DOI: 10.1007/s10792-022-02355-w
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of perioperative problems related to intraocular Implantable Collamer Lens (ICL) implantation

Abstract: Purpose To introduce a modified procedure of ICL implantation, to summarize the perioperative problems and their corresponding treatment after myopia correction with Implantable Collamer Lens (ICL), and to compare the difference of complications between the no-hole ICL and hole ICL. Methods We searched all articles on ICL-related perioperative problems and their corresponding treatment in Scopus, Embase, PubMed and Web of Science databases for the last 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 185 publications
2
22
0
Order By: Relevance
“…As a kind of intraocular refractive surgery, implantable collamer lens (ICL; Staar Surgical, Nidau, Switzerland) implantation has been widely affirmed for its safety and effectiveness in correcting moderate and high myopia [ 3 , 4 ]. However, the intraocular lens is implanted into the posterior ciliary sulcus during ICL implantation, which has a particular impact on the anatomical structure of the anterior segment and may affect the drainage of aqueous humor due to narrowing or closure of the anterior chamber angle (ACA), resulting in elevated eye pressure or secondary glaucoma [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of intraocular refractive surgery, implantable collamer lens (ICL; Staar Surgical, Nidau, Switzerland) implantation has been widely affirmed for its safety and effectiveness in correcting moderate and high myopia [ 3 , 4 ]. However, the intraocular lens is implanted into the posterior ciliary sulcus during ICL implantation, which has a particular impact on the anatomical structure of the anterior segment and may affect the drainage of aqueous humor due to narrowing or closure of the anterior chamber angle (ACA), resulting in elevated eye pressure or secondary glaucoma [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a kind of intraocular refractive surgery, implantable collamer lens (ICL; Staar Surgical, Nidau, Switzerland) implantation has been widely a rmed for its safety and effectiveness in correcting moderate and high myopia [5,6]. However, the intraocular lens is implanted into the posterior ciliary sulcus in the ICL implantation operation, which has a particular impact on the anatomical structure of the anterior segment and may affect the drainage of aqueous humor due to the reduction or closure of the anterior chamber angle (ACA), resulting in elevated eye pressure or secondary glaucoma [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Special consideration must also be given when performing other refractive procedures such as intraocular implantable collamer lenses (ICL) in patients with any degree of glaucoma. A recent review of perioperative complications related to intraocular ICL implantation from Zhang et al [42 ▪ ] reported high IOP and secondary glaucoma among the most common, accounting for 4.4% of all postoperative complications. They reported these outcomes were due to steroid response, pupillary block, iris pigmentation and narrow anterior chamber angle (ACA).…”
Section: Postoperative Considerationsmentioning
confidence: 99%